Design of Solar Thermal District Heating for Andean Region Communities, Based on Chemically Modified Renewable Pcm - Víctor A. Lizcano-Gonzalez; Viatcheslav Kafarov; Andres F. Leon Esteban (Chemical Engineering Transactions)
In Colombia more than 70% of the population lives in areas above 1.000 m above the sea level, with large urban settlements such as the country's capital, with 10 million inhabitants and elevation of 2.600 m. The cold climate of these places creates a high demand for heat throughout the year, especially at nighttime. However, many of these communities have an average annual solar radiation of 4.5 kWh/m2, which allows considering the use of solar thermal storage systems for heat generation. In 2022, the Universidad Industrial de Santander, together with Northumbria University and with financial support from the Royal Society, installed the first solar thermal unit in Colombia, which provides hot water and heating to a rural house located in a highland area. Based on the knowledge acquired, this work presents a novel methodology for the sizing of a solar thermal system for the supply of hot water and heating. This methodology, the first of its kind, allows through the application of basic principles the estimation of the main parameters of the system, including the amount of phase change material required. The proposed system should be capable of supplying the heat demand of 20 rural houses located in high mountain areas, considering the use of vacuum tube-type solar collectors and the use of hydrogenated palm stearin as a novel Phase Change Material (PCM). The daily heat demand for this group of houses was calculated at 1,878 MJ, requiring a minimum of 9,000 kg of PCM and a collection area of 283 m2, using evacuated tube type solar thermal collectors. Therefore, a simple and effective methodology is presented that allows obtaining the main parameters for the sizing of solar thermal systems, being the basis for the simulation of the performance of these systems.